Dépasser l’analogie, écouter les opprimé·es : patriarcat et blanchité dans le discours antispéciste - Myriam Bahaffou (Glad!, 2024)
This article provides an insight about two misuses of the analogy in Animal Ethics: first, the analogy between speciesism and sexism; second, the analogy between the enslavement of Black people in Africa and animal exploitation (which itself serves a broader analogy, between speciesism and racism). On the one hand, the analogy served to establish a relationship between sexism/speciesism without women and through a patriarchal rationalist ethic, although vegan ecofeminists had already rejected similarity for an entangled and dynamic models. Secondly, I argue that the analogy was used to instrumentalize racism, considering racialized people, and black people in particular, as simple examples in order to solidify the argumentative logic of antispeciesism. On the one hand, vegan ecofeminism - through care ethics of in particular- as well as afro-veganism, have demonstrated that those uses of the analogy occurred without any practice of situated knowledge. These two literatures have substituted analogy for other methods of reasoning that enable us to take responsibility towards the subjects involved, outside a reifying and instrumental discourse.